2017
DOI: 10.3892/etm.2017.4698
|View full text |Cite
|
Sign up to set email alerts
|

Allicin improves carotid artery intima-media thickness in coronary artery disease patients with hyperhomocysteinemia

Abstract: Abstract. Homocysteine (Hcy) is an important and independent risk factor for atherosclerotic diseases, such as coronary artery disease and ischemic cerebrovascular disease. Increased carotid artery intima-media thickness (IMT) is a non-invasive marker of systemic atherosclerosis. Allicin treatment may decrease serum Hcy levels and improve impaired endothelial function in rats with hyperhomocysteinemia (HHcy). The present study hypothesized that allicin has an anti-atherosclerotic effect in coronary heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
(19 reference statements)
0
22
0
3
Order By: Relevance
“…Several studies have reported the beneficial effects of garlic in different presentations, such as extracts, lyophilization, and pills. Allicin has demonstrated a plethora of beneficial effects [66][67][68], but the dose used in experimental models, as well as in patients, is between 10 and 40 mg/day, and no secondary effects have been described. However, the use of allicin in patients is limited and focused on triglycerides and cholesterol alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the beneficial effects of garlic in different presentations, such as extracts, lyophilization, and pills. Allicin has demonstrated a plethora of beneficial effects [66][67][68], but the dose used in experimental models, as well as in patients, is between 10 and 40 mg/day, and no secondary effects have been described. However, the use of allicin in patients is limited and focused on triglycerides and cholesterol alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid-lowering, anti-inflammatory, and antioxidative properties are underlying its atheroprotective Targeting Foam Cells by Natural Products effects observed in hyperlipidemic mice and rabbits (Abramovitz et al, 1999;Gonen et al, 2005;Yokoyama et al, 2012). Importantly, allicin (40 mg 3 times daily for 12 weeks) also decreased the carotid intima/media thickness in CAD patients with hyperhomocysteinemia (Liu et al, 2017a). A recent study (Lin et al, 2017) also showed that allicin reduced the TC, FC, and CE levels in THP-1 macrophage-derived foam cells by upregulating the ABCA1-dependent cholesterol efflux via PPARg/ LXRa signaling pathway.…”
Section: G Fatty Acidsmentioning
confidence: 97%
“…Decreased carotid intima/media thickness, decreased homocysteine, TC, and TG in CAD patients with hyperhomocysteinemia (Liu et al, 2017a). Pyranone derivatives: Asperlin Promoted cholesterol efflux from mouse macrophages (Zhou et al, 2017).…”
Section: Namentioning
confidence: 99%
“…Color Doppler ultrasonography is a simple, non-invasive, economical and reproducible tool for the assessment of carotid atherosclerosis (16), and can directly measure the IMT in the absence of changes in hemodynamics an d morphology. Thus, it can predict and detect the early vascular changes in T2DM patients and therefore has been widely used for the assessment of systemic atherosclerosis and cardiovascular risk in adults (17). In this study, on the basis of arteriosclerosis scores, plaque size, PSV and EDV, our results indicated that atherosclerosis is a progressive process in T2DM, even with drug treatment, and treatment is to delay its progression and deterioration.…”
Section: Psv and Edvmentioning
confidence: 56%